Gene polymorphisms that contribute to physical performance in high-speed and power kinds of track and field athletics - Дроздовська [Svitlana Drozdovska] Світлана Богданівна; Бобровник [Volodymyr Bobrovnik] Володимир Ілліч; Криворученко [Olena Krivoruchenko] Олена Вікторівна; Ільїн [Volodymyr Ilyin] Володимир Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
The possibility of improvement of the sports selection to speed and power kinds of track and field athletics with the molecular markers. The aim of the study was to find molecular markers genetic predisposition to the manifestation of physical performance in power kinds of track and field athletics. The significance of differences between group of power kinds of track and field athletics athletes and the control group on the distribution of allele NO-synthase gene polymorphism and distribution of genotype of metalloproteinase 2 gene polymorphism was found. The athletes who specialize in different types are characterized by genetic heterogeneity. Favorable alleles for high athletic performance in speed and power of different kinds of athletics were established.